Efficacy of Seoul National University Renal Stone Complexity Score for Predicting Stone Free Rate after Percutaneous Nephrolithotomy - Haleemullah, Naveed Ahmed Mahar, Mazhar Ali Channa, Ghulam Mustafa Kalhoro, Harris Hassan Qureshi, Sara Rasheed Kalwar, Rehan Mohsen (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of stone clearance following single tract percutaneous nephrolithotomy and evaluate the reliability of the renal stone. Study Design: Descriptive study Place and duration of study: Department of Urology, SIUT, Karachi from 1st January 2020 to 31st October 2021. Methodology: One hundred and forty four patients were enrolled. Patients were classified into three groups, low, medium and high score group based on Seoul Renal Stone Complexity Scoring System. To determine the SFR, all patients were followed with ultrasound and X-ray KUB for 30th day after the surgery. Results: The patients’ mean age was 34.51±12.57 years. The mean SReSC score was 4.00±1.96. There were 106(73.61%) males and 38(26.39%) patients were females. SReSC score was low in 71 patients (49.31%), medium in 45 patients (31.25%), and high in 28 patients (19.44%). 114(79.17%) patients were found to be stone-free. The SFR was greater among patients with a low S-ReSC score 98.6%. Conclusion: The S-ReCSC scoring system is valuable in predicting of the post PCNL stone free rate. Keywords: Seoul National University Renal Stone Complexity Score, Stone free rate, Percutaneous Nephrolithotomy.